Spesialisasi Kegiatan Produksi dan Kemitraan Subkontrak pada Klaster Batik Kota Pekalongan - Aulia Dwi Zulhida; Ragil Haryanto (Jurnal Wilayah dan Lingkungan, 2016)
Pekalongan City has 860 batik industries in 2013 whose development underpinned by specialization and subcontracting partnership patterns. Most of the batik industries do not solely proceed the entire production process, rather they set up a subcontracting partnership with the other specialized industries. The study purposed to determine the production specialization and subcontracting partnership in Pekalongan batik cluster. The study completed by using a quantitative method with descriptive quantitative analysis. The results showed that the majority of Pekalongan batik industry is stamping batik, covering 82% share of the entire batik industries. The specialization consisted of batik production, convection, and canting production. These specializations geographically grouped into subclusters due to endowment factor, such as labor, land, and infrastructure. The specialization of production also led to subcontracting partnership in the batik cluster which was known as speciality subcontracting. The subcontracting partnership has negative and positive impacts, such as the dependence of the subcontractors to their principals, the efficiency in production factors, and cost efficiency.It shows that the production specialization and subcontracting partnership in Pekalongan batik cluster are mutually interconnected.